A túlélés kockázata. A megyerendszer közigazgatási és hatalompolitikai szerepének összefüggése Magyarhonban - Horváth M., Tamás (Tér és Társadalom, 1989)
The middle levels of administration have their own natural history. In Unitarian states it is particularly difficult to define the justification of the spatial system or spatial breakdown above the local level. Nevertheless, it remains a question to be answered in a research into either the present impacts of historical borders or the relevance of more and more recent regional connections. The system of counties is a particularly petrified one in Hungary. It grew out of its own role consecutively in the time of feudalism, capitalism and also later, following World War II. Thereby it was successively becoming the means of central policies which, in turn, wanted to restrict local governmental independence, or to put it out of action. In the time of historically dragging Hungarian feudalism the county also served as organizational frameworks for the smaller nobility (below baron’s rank and above the commoner). As, in lack of developed bourgeoisie, this stratum headed the bourgeois transformation during the first half of the 19th century, the prominent role of the county system remained intact. Albeit the feudal determinants of public administration disappeared by the 1870s, the system of counties preserved its privileges which later proved to be irremovable. The county administration became the major basis of the gentry which lost its fortune but wanted to preserve the prestige. The preservation of privileges also favoured the weak Hungarian bourgeoisie not accustomed to free competition. Since an important part of bourgeois selfgovernmental functions was concentrated at the level of counties, spontaneous relationships among settlements and their societies could not develop in an organic way. The so-called socialist development has preserved these frameworks during the post-war period. The communist party neither dared nor intended to mobilize the forces inherent in the countryside. At the same time, maintaining the county system was looked upon as a means to reach a completely new goal, namely: county institutions were buílt up to serve as an element of unlimited centralization. From the 1960s onwards, a somewhat less centralized model of administration evolved in Hungary which built upon counties as self-reliant political sub-centres. By the 1970s, while self-government was repeatedly insisted upon, veritable petty ’monarchies’ have developed headed by county party chiefs. Thus in Hungary, for historical reasons, the system of counties has always been the means of centralization. It kept producing hierarchical positions which could not be controlled by the local population. For this reason, the Hungarian county system is to be abolished in the future. This radical step is justified because if only its functions were reduced, the non-hierarchical county of the Western type could never develop. The deeply rooted monolith official-political mechanism of counties would outlive its time despite all positive political changes in Hungary. How is this radical step possible? First a wide range of county functions is to be abolished, partly because many among them have become unnecessary as state functions. Some of the remaining ones could be provided by local governments, either themselves or via their associations. At present, Hungarian counties are characterized by the accumulation of state power functions. In order to stop this, administrative courts are to be set up. In this way judgements on appeals in public proceedings and the protection of self-governmental rights would get out of the sphere of administration. Instead of the present official-principal control, control over local governments, on legal grounds, should be exercised by an independent public prosecutor who is out of the official hierarchy. Middle-level services (secondary school, hospital, home for the elderly) are to be organized by a complex spatial association for the maintenance pf institutions, (tank force). The remaining, purely administrative, functions should be provided by decentralized state organs. In this way the county is to become a mere spatial unit of state administration which defines an area of official jurisdiction. Spatial links among settlements–regiorwlization–should develop spontaneously, only the means are to be ascertained: independent management of local governments and a wide variety of their associations are needed as institutional preconditions. M for the central government, it should pursue regional policy in an indirect way, with the help of a non-hierarchical system of means. In a small country like Hungary such a policy does not require hierarchical subcentres.